In vivo effects of a new dentifrice containing 1.5% arginine and 1450 ppm fluoride on plaque metabolism - Wolff, M; Corby, P; Klaczany, G; Santarpia, P; Lavender, S; Gittins, E; Vandeven, M; Cummins, D; Sullivan, R (The Journal of clinical dentistry, 2013)
This paper presents the results of a clinical study assessing the in vivo effects on plaque metabolism of a new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride compared to a commercially available dentifrice containing 1450 ppm fluoride alone. A four-week, parallel, randomized, double-blind clinical study using 54 subjects was conducted at the New York University College of Dentistry Bluestone Center for Clinical Research. Two study groups used the following products for two weeks: 1) a dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride as sodium monofluorophosphate (MFP; test); and 2) a commercial silica dentifrice with 1450 ppm fluoride as sodium fluoride (NaF; control). In the following two-week period, all subjects used the control product. The effects of product use on plaque metabolism in vivo were assessed by conducting ex vivo analyses at baseline, after two weeks of assigned product use, and after two weeks of control product use. These plaque analyses comprised pH measurements before and after an in vivo sucrose rinse, and measurements of ammonia production and lactate production. The study showed that subjects using the test dentifrice, containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, had significantly higher plaque pH values before the sucrose challenge than those using the commercially available control dentifrice (p < or = 0.01). Plaque samples from subjects using the arginine-containing dentifrice also produced significantly higher levels of ammonia (p < or = 0.01). Subjects using the arginine-containing dentifrice also had a directionally higher plaque pH after the sucrose challenge, and their plaque samples produced a directionally lower level of lactate during the two-week treatment period compared to subjects using the control dentifrice. Following two weeks of subsequent use of the control product, there were no significant differences in plaque metabolism measures between groups. A new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride has been shown in this study to modulate plaque metabolism, increasing ammonia production and decreasing lactate production, thereby increasing plaque pH to help restore a pH-neutral environment.